Case Report: Morbus Hansen Type BB With Type I Leprosy Reaction With Positive Leprosy Cardinal Sign - Prayitno, Yurid Izzati Khairunnissa; Dharmasanti, Prasti Adhi (Sean Institute, 2024)
Morbus Hansen ( leprosy ) is an infectious disease caused by Mycobacterium leprae and can cause disability if not treated properly. Leprosy reactions are divided into type 1 and type 2 (erythema nodosum leprosum) reactions, which differ depending on the type of immunity involved. We report the case of a 21-year-old man from Papua, a leprosy endemic area, who developed red patches accompanied by pain on the hands, feet and ears. Physical examination revealed a “punch out” lesion with erythematous nodes, hypoesthesia, firm borders, and scaling. Thickening of the auricularis magnus sinistra nerve was also found. The diagnosis of Morbus Hansen type BB with type 1 reaction was made based on positive BTA (B1/MI 2+/2%) and positive anti PGL-1 IgM and IgG. Risk factors such as stress and physical fatigue are thought to worsen the patient's condition. Management of type 1 reactions requires appropriate therapy along with control of risk factors to prevent recurrence. Leprosy and its reactions can cause complications that reduce the patient's quality of life. Therefore, effective screening examinations are needed, especially in individuals entering educational institutions, to prevent the spread of the disease. This report highlights the importance of early diagnosis through proper history taking, physical examination and supportive measures to optimize therapy and prevent further complications.